Ophthalmic Features of Schopf-Schulz-Passarge Syndrome - Manpreet Singh; Manpreet Kaur; Aditi Mehta Grewal; Zoramthara Zadeng; Pankaj Gupta (Delhi Journal of Ophthalmology)
Schopf–Schulz–Passarge syndrome (SSPS) is an ectodermal dysplasia of autosomal recessive inheritance. The SSPS involves two or more of the following structures: sweat glands, hair, teeth, nails, and other ectodermal structures. The features of this syndrome constitute multiple periocular and eyelid apocrine hidrocystomas, palmoplantar keratoderma, hypodontia, hypotrichosis, and nail dystrophy. We present pictorial description of the SSPS.